2013
DOI: 10.1007/s00134-013-3069-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the learning curve for ultrasound-guided jugular central venous catheter placement

Abstract: Our study demonstrates that skills in US-guided CVC placement can easily be acquired with training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 14 publications
1
46
0
2
Order By: Relevance
“…9 With respect to skills such as USG CVC insertion there is, however, a paucity of evidence for the specific type and volume of simulator practice required to achieve technical proficiency. 2,10 Residency programs would benefit from evidence of this nature to guide the design of competency-based curricula, as it could inform such things as the number of practice sessions to schedule and the most effective forms of practice.…”
Section: Introductionmentioning
confidence: 99%
“…9 With respect to skills such as USG CVC insertion there is, however, a paucity of evidence for the specific type and volume of simulator practice required to achieve technical proficiency. 2,10 Residency programs would benefit from evidence of this nature to guide the design of competency-based curricula, as it could inform such things as the number of practice sessions to schedule and the most effective forms of practice.…”
Section: Introductionmentioning
confidence: 99%
“…In adults and children, ultrasound‐guided central venous catheterization has a higher success rate than the landmark technique . Moreover, ultrasound‐guided vascular access skill can be acquired easily by novice trainee …”
mentioning
confidence: 99%
“…showed that 41% of the programs have no minimum requirement for NTHDC placement . The argument for having a minimum number of procedure requirements is based on studies that show improvement in procedural skills with repeated line placement . However, it is unclear what the optimal number of NTHDC performed should be before someone can be certified to be “competent” as the learning curve for each individual is different.…”
Section: Acute Dialysis Access‐the General Nephrology Experiencementioning
confidence: 99%
“…6 The argument for having a minimum number of procedure requirements is based on studies that show improvement in procedural skills with repeated line placement. 16 However, it is unclear what the optimal number of NTHDC performed should be before someone can be certified to be "competent" as the learning curve for each individual is different. Moving towards a more competency-based system would be better where learners practice until they reach a predetermined achievement standard regardless of how many attempts it takes to get these results.…”
Section: Introductionmentioning
confidence: 99%